2000
DOI: 10.1063/1.372277
|View full text |Cite
|
Sign up to set email alerts
|

Electrical conductivity effects in polyethylene terephthalate films

Abstract: Influence of the relaxation of Maxwell-Wagner-Sillars polarization and dc conductivity on the dielectric behaviors of nylon 1010Electrical conductivity effects in biaxially stretched polyethylene terephthalate ͑PET͒ films of 6 m thickness and 68% degree of crystallinity were investigated by means of dielectric relaxation spectroscopy in the frequency range 10 Ϫ2 -10 6 Hz and at temperatures higher than the glass transition temperature ͑ϳ85°C͒ up to 190°C. The formalisms of complex permittivity, electric modulu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
43
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 45 publications
5
43
0
1
Order By: Relevance
“…8a) and the best fit line to the data It is known that the T g of PET changes from 351 K for the amorphous material to 398 K for the biaxially stretched semi-crystalline material [19,23]. Differential Scanning Calorimetry (DSC) measurements on the same sample showed a broad and weak glass-rubber transition in the range 343-393 K, in agreement with dielectric relaxation spectroscopy (DRS) studies [16,19,24] and the present results. Taking into account these studies, the TSDC spectrum in Fig.…”
Section: Experimentally Measured Tsdc Spectrasupporting
confidence: 78%
See 2 more Smart Citations
“…8a) and the best fit line to the data It is known that the T g of PET changes from 351 K for the amorphous material to 398 K for the biaxially stretched semi-crystalline material [19,23]. Differential Scanning Calorimetry (DSC) measurements on the same sample showed a broad and weak glass-rubber transition in the range 343-393 K, in agreement with dielectric relaxation spectroscopy (DRS) studies [16,19,24] and the present results. Taking into account these studies, the TSDC spectrum in Fig.…”
Section: Experimentally Measured Tsdc Spectrasupporting
confidence: 78%
“…DRS studies, on the same material and in the same temperature range, have showed that the dielectric peak corresponding to the primary α-relaxation is very broad and can not be described by a single Debye peak [16,19,20]. The fact that the peak in Fig.…”
Section: Experimentally Measured Tsdc Spectramentioning
confidence: 83%
See 1 more Smart Citation
“…The non constant part of the σ ac spectrum at LF/HT shifts towards higher frequencies with increasing the temperature, leading to an increase in the charge carrier mobility. The EP therefore tends to be superimposed on the dc bulk conductivity σ dc [21][22][23][24].…”
Section: Fig 1 (Color Online)mentioning
confidence: 99%
“…To have a proper assignment of the peak we have to recall that the AC dielectric measurements on the same material [15] indicate that the a relaxation appears as a weak and broad peak in imaginary part of the permittivity e 00 at a temperature around 100°C in the Hz-kHz frequency range. At room temperature, the b relaxation in the amorphous phase in observed in the kHz frequency range while the b relaxation in the crystalline phase is just entering at the lower limit of frequency range of 0.01 Hz.…”
Section: Resultsmentioning
confidence: 99%